Reimagining operational excellence inspirations from Asia - Kotler, Philip; Kartajaya, Hermawan 1947-; Mussry, Jack (Ascent Audio, 2024)
In Reimagining Operational Excellence: Inspirations From Asia, world-renowned marketing guru and bestselling author Philip Kotler delivers a groundbreaking book unveiling the transformative marketing strategies that have propelled Asia to the forefront of the global business arena. In this insightful work, Kotler explores the dynamic competition between Asia and the global West, revealing how it has catalyzed Asia's adoption of incisive and effective marketing practices. The book delves into various dimensions of marketing operations, including quality, cost, delivery, service, creativity, and innovation, highlighting the crucial role of entrepreneurship and leadership in achieving operational excellence. Kotler's analysis extends to significant developments within the global business ecosystem, showcasing how countries like Singapore, Japan, Korea, India, and China are redefining business efficiency and continuous improvement. You'll also find in-depth examinations of China's unique and competitive economic ecosystem; discussions of the increasingly foundational role played by Singapore as an international business hub; and an analysis of the latest economic developments in South Korea driving marketing excellence in that country.
Online resource; title from title details screen (O'Reilly, viewed October 29, 2024)
Keywords: Marketing -- Management; Marketing -- Asia; Marketing; Gestion; Marketing; Asie; Audiobooks; Livres audio